2013
DOI: 10.1590/0074-0276108052013016
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic species of Paracoccidioides brasiliensis: impact on paracoccidioidomycosis immunodiagnosis

Abstract: We aimed to evaluate whether the occurrence of cryptic species of Paracoccidioides brasiliensis, S1, PS2, PS3 and Paracoccidioides lutzii, has implications in the immunodiagnosis of paracoccidioidomycosis (PCM). Small quantities of the antigen gp43 were found in culture filtrates of P. lutzii strains and this molecule appeared to be more variable within P. lutzii because the synonymous-nonsynonymous mutation rate was lower, indicating an evolutionary process different from that of the remaining genotypes. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 33 publications
0
19
0
1
Order By: Relevance
“…This is a new species in the Paracoccidioides genera recently described that is endemic in some areas of South America where the patients' sera were reported to not recognize the P. brasiliensis' antigens in conventional serological tests [27][29]. This issue could not be addressed here since the 6 reference centers participating in the study were located in P. brasiliensis endemic areas and provided sera only with positive serological results.…”
Section: Resultsmentioning
confidence: 98%
“…This is a new species in the Paracoccidioides genera recently described that is endemic in some areas of South America where the patients' sera were reported to not recognize the P. brasiliensis' antigens in conventional serological tests [27][29]. This issue could not be addressed here since the 6 reference centers participating in the study were located in P. brasiliensis endemic areas and provided sera only with positive serological results.…”
Section: Resultsmentioning
confidence: 98%
“…Teixeira et al found morphologic variations between conidia of complex P. brasiliensis and P. lutzii (27). Studies evaluating double immunodiffusion (DID) test with sera from patients infected by different cryptic species complex P. brasiliensis and P. lutzii revealed wide variation in reactivity, suggesting significant differences among these fungi (12,28,29). In 2016, Siqueira et al found distinct patterns of host-parasite interaction and pathology caused by P. brasiliensis and P. lutzii (10).…”
Section: Discussionmentioning
confidence: 99%
“…PCM can be caused by fungi of the Paracoccidioides genus, comprising P. brasiliensis complex, consisting of four cryptic species (S1, PS2, PS3 and PS4) (2,3,12) and P. lutzii. (initially Pb01, a new clade) (3,6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, infections reported in endemic areas of P. lutzii frequently present lymphatic-abdominal clinic manifestation, which are not reported in areas endemic for the P. brasiliensis species complex [10]. Also, sera recovered from patients infected with P. lutzii are not recognized by P. brasiliensis antigens and conversely [8, 1113].…”
Section: Introductionmentioning
confidence: 99%